Speleothem record from Pentadactylos cave (Cyprus): new insights into climatic variations during MIS 6 and MIS 5 in the Eastern Mediterranean - Nehmé, Claude; Kluge, Tobias; Verheyden, S.; Nader, F.; Charalambidou, I.; Weißbach, Therese; Gucel, S.; Cheng, H.; Edwards, R. L.; Satterfield, L.; Eiche, E.; Claeys, Ph (Quaternary science reviews, 2020)
A new paleoclimate record from Cyprus gives valuable insights into climatic variations during Marine Isotope Stages (MIS) 6-5 for the East Mediterranean region. Two stalagmites from Pentadactylos cave in the Kyrenia mountain range (800 m altitude) in Cyprus grew from 174.6 ± 0.7 to 112.2 ± 0.5 ka BP with major hiatuses at 163-142 and 132-128 ka. During early MIS6 the stalagmite suggests through a relatively low growth rate (57-5 mm/ka) and variable, but rather negative d18O that climate conditions were highly variable on a millennial scale, with wet and cold climate conditions during Sapropel 6 deposition. At the end of MIS6 (141-132 ka), growth rate varied from 123 to 18 mm/ka and less negative δ 18 O c suggests general dry/cold conditions followed by a growth stop during H11. The onset of MIS5e is marked by the highest growth rate (217 mm/ka). The most negative δ18O values at the onset and during the Eemian wet period in Cyprus are driven mostly by the source effect (Sapropel 5) and enhanced rainfall amounts. Stable conditions during MIS 5e were rather short as shown in the growth and isotopic signal, consistent with other EM records. After 122 ka, growth decreased drastically (8-2 mm/ka) and a slow deterioration of the soil cover is suggested from continuously less negative δ13C values. Fluid inclusion d18O shows a clear shift (4-5‰) between end-MIS 6 and MIS 5e. Clumped isotopes measurements indicate kinetic effects between calcite and water of up to ∼1‰. After correction for kinetic effects using Δ47, a minimum estimate for the MIS 6-5 temperature shift in the EM is ca. 9 °C. Similarly, drastic changes in rainfall amounts are inferred from measured (fluid inclusion) and calculated water d18O.